Case of post‐orgasmic illness syndrome associated with hypogonadism - Takeshima, Teppei (IJU Case Rep, 2020)
INTRODUCTION: Post‐orgasmic illness syndrome is a rare condition that occurs after ejaculation and persists for 2–7 days and is characterized by flu‐like symptoms, which can significantly reduce quality of life. CASE PRESENTATION: A 21‐year‐old unmarried man was referred to our hospital due to flu‐like symptoms that developed after ejaculation by masturbation and persisted for about 2 days. The patient’s free testosterone level was slightly lower than normal. Nonsteroidal anti‐inflammatory drugs were initially administered and helped relieve headache and muscle pain. Thereafter, the patient was able to ejaculate three times a week. In addition, after administering testosterone enanthate once or twice a month, his general fatigue significantly improved, and he could ejaculate every day. CONCLUSION: The pathophysiology of post‐orgasmic illness syndrome has not been fully elucidated. The treatments for this condition must be accurately selected according to pathophysiology.